Information system IAPS 4.0 using fuzzy logic decision support system for study program accreditation / Ahmad Fashiha Hastawan, Dhidik Prastiyanto and Riska Dami Ristanto - Hastawan, Ahmad Fashiha; Prastiyanto, Dhidik; Ristanto, Riska Dami (Faculty of Computer and Mathematical Sciences, 2012)
Instrumen Akreditasi Program Studi (IAPS) is an instrument and guideline for study program accreditation formulated by the National Accreditation Board for Higher Education (BAN-PT). The change from IAPS 3.0 to IAPS 4.0 makes every study program in all universities in Indonesia have problems in the form of adjusting accreditation application procedures and assessment simulations that need to be adjusted to changes in the Study Program Accreditation Instrument. From these problems, we made a concept and system design that adopted the rules of the IAPS 4.0 assessment by involving relevant stakeholders and will be tested in each study program that is applying for accreditation. The research method focuses on two parts, namely the system development method with the Waterfall model and the Decision Support System (DSS) method using the Fuzzy Logic method. This method has advantages: it is more efficient in computational problems, works best for linear techniques, works best for optimization and adaptive techniques, and ensures continuity of the output surface. The IAPS 4.0 Information System design using the Fuzzy Logic DSS for Study Program Accreditation is expected to be the right and effective solution for universities in providing solutions to existing problems.